Kompetensi Orangtua dalam Penumbuhkembangan Jiwa Kewirausahaan pada Anak Usia Dini - Desyanty, Ellyn Sugeng (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2016)
Early childhood education became the foundation for adults to develop the intellectual and emotional intelligence and character of the child. Education for every person starts throughout the lifetime of that since the person is in the womb until later headed to the grave. Family and parents to be first educators and foremost for the child who has the responsibility to play a role in designing the learning activities of the child when outside of school, so that learning activities time with educators (teachers) in schools can be integrated with the educational time with parents. Entrepreneurship education as one of education program soft skills can be one of the programs of learning which can form the character of children so that they are ready to grow and develop as a social being in accordance with the development of the world.